1994
DOI: 10.2307/1591850
|View full text |Cite
|
Sign up to set email alerts
|

A Survey into the Prevalence of Poultry Helminths in Northwest Arkansas Commercial Broiler Chickens

Abstract: A 12-month survey was conducted to determine the prevalence of poultry helminths in Northwest Arkansas commercial broiler chickens. Intestinal tracts from market-ready broilers were collected weekly from two commercial broiler companies; a total of 3542 intestinal tracts were collected for parasite enumeration from 67 company A and 52 company B farms. Ascaridia galli was found on 37.3% of company A farms and 3.9% of company B farms, Raillietina cesticillus was found on 67.2% of company A farms and 69.2% of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 4 publications
4
4
0
Order By: Relevance
“…It shows high prevalence especially in free range chickens in rural areas (Wilson et al 1994). The observed prevalence (16.94 %) of Ascaridia galli in the current study was in agreement with the prevalence reported in guinea fowls in South Africa (Mwale and Masika 2011; Table 6).…”
Section: Discussionsupporting
confidence: 91%
“…It shows high prevalence especially in free range chickens in rural areas (Wilson et al 1994). The observed prevalence (16.94 %) of Ascaridia galli in the current study was in agreement with the prevalence reported in guinea fowls in South Africa (Mwale and Masika 2011; Table 6).…”
Section: Discussionsupporting
confidence: 91%
“…Clearly, practices and conditions distinct to each company were critical in determining the magnitude of parasite populations, with conditions that opti- mized the epidemiology of one helminth optimizing the others as well. A similar significant "company effect" in regard to parasite incidence and magnitude was seen earlier in a survey of helminths in broiler chickens [12]. Parasite levels by grower ranking (a production efficiency descriptive consistent for each company) are given in Table 3.…”
Section: Resultssupporting
confidence: 73%
“…Therefore, the time of sampling probably accounted for the present finding of high infection rate but low FECs, since the examined hens were 72 weeks old and were at the end of their laying period. The lack of appreciable clinical signs, gross pathological lesions, and impact on production level in course of heterakiasis has also been reported in commercial broiler chickens (Wilson et al, 1994) and in turkeys parasitized by H. gallinarum alone (Brener et al, 2006). Nevertheless, the pathogenicity of H. gallinarum may vary among hosts as documented in various avian species.…”
Section: Resultsmentioning
confidence: 86%
“…Reported prevalence rates in chickens range from 10.2% to 72.5% in Europe (Kokozidou and Zafeires, 1996;Permin et al, 1999), <1 to 84% in the U.S.A. (Waters et al, 1994), and 17.28 to 78.8% in Africa (Permin et al, 1997;Eshetu et al, 2001), with 1.9-7.5% of the farms (Wilson et al, 1994) and 7-100% of the flocks (Waters et al, 1994) being infected. H. gallinarum infections linked to histomoniasis have been well documented in chickens (Homer and Butcher, 1991;Permin, 2003).…”
Section: Introductionmentioning
confidence: 99%